INDUCTION OF OVULATORY ESTRUS USING OVSYNCH PROTOCOL AND SUBSEQUENT FERTILITY IN TRUE ANESTRUS BUFFALO HEIFERS - GHUMAN, S P S; SINGH, JAGIR; HONPARKHE, M; DADARWAL, D (The Indian Journal of Animal Reproduction, 2023)
The aim of using Ovsynch protocol in true anestrus buffalo heifers (n=11) was to induce synchronized ovulatory estrus and thereafter, to assess the first service conception rate. ’Ovsynch’ involved administration of a GnRH-analogue at days O and 9, and a PGF2alpha analogue on day 7. Transrectal ovarian ultrasonography and jugular vein blood sampling was done daily starting from first-GnRH till ovulation after second-GnRH. Thereafter, these procedures were performed on days 5, 10, 15, 21 and 42 post-ovulation. Heifers were inseminated on day 10 and if required on day 11. In response to firstGnRH, all the heifers ovulated (P<0.05) within 4 days (1.82±0.44 days) with subsequent development of corpus luteum (CL). All the heifers responded (P<0.05Tto PGF2alpha on day 7. Subsequent to secondGnRH (day 9), all the heifers exhibited -estrus symptoms (P<0.05) which disappeared in the event of ovulation (P<0.05) between days 10 and 11 (n=9) or between days 11 and 12 (n=2). First service conception rate after Ovsynch protocol was poor (18%, P<0.05). Post-Ovsynch luteal profile showed comparable CL growth in all the heifers, except on day 21 and 42 (P<0.05-0.10) when CL was small in non-pregnant heifers. Plasma progesterone was sub-optimal on day 5 (P<0.05) in heifers that failed to conceive. In conclusion, Ovsynch protocol was 100% successful for inducing ovulatory estrus which was synchronized in 82% anestrus buffalo heifers, thus requiring insemination only at 24 h subsequent to second-GnRH. More studies should be planned to suggest strategies for improving the first service conception rate in anestrus buffalo heifers subjected to Ovsynch protocol during summer season.